2006
DOI: 10.1021/jp063826h
|View full text |Cite
|
Sign up to set email alerts
|

Silver Colloid Nanoparticles:  Synthesis, Characterization, and Their Antibacterial Activity

Abstract: A one-step simple synthesis of silver colloid nanoparticles with controllable sizes is presented. In this synthesis, reduction of [Ag(NH(3))(2)](+) complex cation by four saccharides was performed. Four saccharides were used: two monosaccharides (glucose and galactose) and two disaccharides (maltose and lactose). The syntheses performed at various ammonia concentrations (0.005-0.20 mol L(-1)) and pH conditions (11.5-13.0) produced a wide range of particle sizes (25-450 nm) with narrow size distributions, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
1,136
8
24

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,121 publications
(1,220 citation statements)
references
References 43 publications
52
1,136
8
24
Order By: Relevance
“…Additionally, the silver nanoparticles showed good inhibition activity towards C. albicans. The mechanism of inhibitory action of silver nanoparticles on microorganisms is not very well known [28,29] . However, several mechanisms have been proposed to explain the inhibitory effect of silver nanoparticles on bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the silver nanoparticles showed good inhibition activity towards C. albicans. The mechanism of inhibitory action of silver nanoparticles on microorganisms is not very well known [28,29] . However, several mechanisms have been proposed to explain the inhibitory effect of silver nanoparticles on bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Metal and metal oxide NPs have been introduced in many products with many different purposes. For example, they have been used in consumer products such as sunscreens and cosmetics (ZnO and TiO 2 ) [11,12], detergents and antibacterials (Ag) [13][14][15][16][17], paints (TiO 2 and Ag) [18,19], printer inks (Ag and Au) [20], and textiles (Ag) [13,21]. The applications of NPs also include electronics, medicine, chemistry, catalysis, and fuel additives [22].…”
Section: Sources Of Metal-based Nps In Soilmentioning
confidence: 99%
“…Some of the silver nanoparticles also penetrate into the cells. It is reported that the bactericidal effect of silver nanoparticles decreases as the size increases and is also affected by the shape of the particles [23,24]. Although most studies have utilized spherical particles, truncated triangular shaped particles are reported to have greater bactericidal effect compared to that of spherical and rodshaped particles [24].…”
Section: Introductionmentioning
confidence: 99%